1997
DOI: 10.1029/97jd01122
|View full text |Cite
|
Sign up to set email alerts
|

Observations of aerosols in the free troposphere and marine boundary layer of the subtropical Northeast Atlantic: Discussion of processes determining their size distribution

Abstract: Abstract. During July 1994, submicron aerosol size distributions were measured at two sites on Tenerife, Canary Islands. One station was located in the free troposphere (FT), the other in the marine boundary layer (MBL). Transport toward these two sites was strongly decoupled: the FT was first affected by dust and sulfate-laden air masses advecting from North Africa and later by clean air masses originating over the North Atlantic, whereas the MBL was always subject to the noaheasterly trade wind circulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 33 publications
8
96
0
1
Order By: Relevance
“…Hence most of the non-sea salt sulfate aerosol in the MBL must originate from other locations. Indeed, model studies Raes, 1995) and observations (Clarke et al, 1996;Raes et al, 1997;Bates et al, 1998) have explained MBL aerosol concentrations with entrainment from the free troposphere. Katoshevski et al (1999) even concluded that MBL aerosol number concentration is dominated by aerosol from the free troposphere under virtually all conditions.…”
Section: Sources Of Marine Boundary Layer Aerosolmentioning
confidence: 99%
“…Hence most of the non-sea salt sulfate aerosol in the MBL must originate from other locations. Indeed, model studies Raes, 1995) and observations (Clarke et al, 1996;Raes et al, 1997;Bates et al, 1998) have explained MBL aerosol concentrations with entrainment from the free troposphere. Katoshevski et al (1999) even concluded that MBL aerosol number concentration is dominated by aerosol from the free troposphere under virtually all conditions.…”
Section: Sources Of Marine Boundary Layer Aerosolmentioning
confidence: 99%
“…2,000 Clarke et al [1997] midlat free trop (Atl) 6,000 O'Dowd et al [1997] Weddell Sea MBL (Antarctic) 4,300 Raes et al [1997] subtropical free trop, cloud free 4,000 Schröder and Ström [1997] midlat cont UT 10,000 Thornton et al [1997] tropical UT, near convection 18,000 Weber et al [1997] and Eisele and McMurry [1997] midlat clean cont, free trop air 600…”
Section: Observationsmentioning
confidence: 99%
“…Concerns related to the potential effects of these small aerosols on human health, visibility, and climate have initiated studies on the formation an evolution of ultrafine particles (UFP), which in this work denote aerosol particles with d p < 100 nm. Using instruments that can detect particles with diameters as low as 3 nm, UFP have been documented in the free troposphere [Clarke et al, 1998;Raes et al, 1997;Schröder and Ström, 1997] and in the vicinity of clouds [Hegg et al, 1991]. Significant evidence of nucleation of new particles was found at continental boundary layer sites [Birmili and Wiedensohler, 2000;Verheggen and Mozurkewich, 2002;Birmili et al, 2003], including boreal forests [Mäkelä et al, 1997;Kulmala et al, 1998Kulmala et al, , 2001aKulmala et al, , 2001bKomppula et al, 2003] and Arctic regions [Wiedensohler et al, 1996;Pirjola et al, 1998].…”
Section: Introductionmentioning
confidence: 99%